2019
DOI: 10.1097/gme.0000000000001161
|View full text |Cite
|
Sign up to set email alerts
|

Serum androgen profiles in women with premature ovarian insufficiency: a systematic review and meta-analysis

Abstract: Women with premature ovarian insufficiency are at risk for decreased concentrations of testosterone, dehydroepiandrosterone sulfate, and androstenedione. Dehydroepiandrosterone sulfate levels were more reduced in postmenopausal controls when compared with premature ovarian insufficiency cases.This is an open access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permissible to download and share the work provided it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 50 publications
1
16
0
1
Order By: Relevance
“…Because of its impact on well-being, loss of fertility, selfesteem, body image, sense of femininity, and other aspects of health, POI may adversely affect a woman's relationship with her partner, the quality of intimacy, and even a woman's motivation to start a new relationship 98 . Aside from reproductive function and psychosocial aspects contributing to sexual dysfunction, women with POI may experience reduced androgen production in addition to the loss of estrogen 99,100 . Because androgens are believed to play an important role in sexual functioning in women, and trials of testosterone treatment in women have shown improvements in sexual function 101 , loss of androgens may have a negative impact on sexual functioning.…”
Section: Sexual Healthmentioning
confidence: 99%
“…Because of its impact on well-being, loss of fertility, selfesteem, body image, sense of femininity, and other aspects of health, POI may adversely affect a woman's relationship with her partner, the quality of intimacy, and even a woman's motivation to start a new relationship 98 . Aside from reproductive function and psychosocial aspects contributing to sexual dysfunction, women with POI may experience reduced androgen production in addition to the loss of estrogen 99,100 . Because androgens are believed to play an important role in sexual functioning in women, and trials of testosterone treatment in women have shown improvements in sexual function 101 , loss of androgens may have a negative impact on sexual functioning.…”
Section: Sexual Healthmentioning
confidence: 99%
“…Despite controversial results in the literature, many women with POI may present low serum testosterone levels when compared to non-POI women of the same age. (24,25,(27)(28)(29)(30)(31) Although this testosterone deficiency seems to contribute to the manifestation of POI, there is not enough evidence to recommend routine testosterone administration or replacement therapy in these patients. (22,32) Premature ovarian insufficiency: A hormonal treatment approach Testosterone can be currently prescribed for women with POI diagnosed with hypoactive sexual desire disorder with no contraindication.…”
Section: How To Monitor and Follow Up Women With Poi?mentioning
confidence: 99%
“…Diminished ovarian reserve (DOR) is a common cause of otherwise unexplained infertility, as well as, early ovarian hor-monal insufficiency and related endocrinopathies. Recently published meta-analysis that included 14 studies shows that individuals with premature ovarian insufficiency (POI) have lower concentration levels of androgens in comparison with healthy controls: DHEAS, testosterone and androstendione [40]. Others estimated that suboptimal DHEAS concentrations are quite common and were found in 65% of women with diminished ovarian reserve DOR [41].…”
Section: Supplementation Of Dhea For Fertility Improvementmentioning
confidence: 99%